Pengaruh Laju Pertumbuhan Ekonomi, Tingkat Partisipasi Angkatan Kerja, dan Rata-Rata Lama Sekolah Terhadap Pengangguran - Bachri, Diva Agatha; Salmah, Emi (Journal of Trends Economics and Accounting Research, 2025)
This study aims to examine the impact of economic growth, labor force participation rate, and average years of schooling on the unemployment rate in West Nusa Tenggara Province from 2019 to 2023. The research methodology used is quantitative research. This study utilizes secondary data obtained from the Central Statistics Agency (BPS). This investigation uses E-Views software version 12, using a panel data regression method based on the Random Effect Model (REM) methodology. The research findings indicate that the economic growth variable has a negative but small impact on the unemployment variable. The labor force participation rate shows a negative but significant impact on unemployment. Simultaneously, the variable representing the average years of schooling shows a beneficial impact although statistically negligible on unemployment. The results of the simultaneous test (F test) reveal a probability value (F-statistic) of 0.019817, which is smaller than 0.05, and an Adjusted R-squared value of 0.138321, or 13.83%. This indicates that the independent variables of economic growth rate, labor force participation rate, and average years of schooling simultaneously have a significant influence on the dependent variable, the open unemployment rate. Other factors are influenced by complementary variables not examined in this study. This study aims to examine the impact of economic growth, labor force participation rate, and average years of schooling on the unemployment rate in West Nusa Tenggara Province from 2019 to 2023. The research methodology used is quantitative research. This study utilizes secondary data obtained from the Central Statistics Agency (BPS). This investigation uses E-Views software version 12, using a panel data regression method based on the Random Effect Model (REM) methodology. The research findings indicate that the economic growth variable has a negative but small impact on the unemployment variable. The labor force participation rate shows a negative but significant impact on unemployment. Simultaneously, the variable representing the average years of schooling shows a beneficial impact although statistically negligible on unemployment. The results of the simultaneous test (F test) reveal a probability value (F-statistic) of 0.019817, which is smaller than 0.05, and an Adjusted R-squared value of 0.138321, or 13.83%. This indicates that the independent variables of economic growth rate, labor force participation rate, and average years of schooling simultaneously have a significant influence on the dependent variable, the open unemployment rate. Other factors are influenced by complementary variables not examined in this study.